2015
DOI: 10.1161/circimaging.114.002769
|View full text |Cite
|
Sign up to set email alerts
|

Association of Left Atrial Function and Left Atrial Enhancement in Patients With Atrial Fibrillation

Abstract: Background Atrial fibrillation (AF) is associated with left atrial (LA) structural and functional changes. Cardiac magnetic resonance (CMR) late gadolinium enhancement (LGE) and feature-tracking are capable of noninvasive quantification of LA fibrosis and myocardial motion, respectively. We sought to examine the association of phasic LA function with LA enhancement in patients with AF. Methods and Results LA structure and function was measured in 90 AF patients (age 61 ± 10 years, 76% male) referred for abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 35 publications
10
112
2
4
Order By: Relevance
“…In fact, Habibi et al found that hypertensive patients with LA enhancement were more inclined to persistent or permanent atrial fibrillation. 29 Therefore, our study adds to the current knowledge by providing new functional issues in patients with similar LV hypertrophy, but different pathophysiology, in an attempt to improve the therapeutic approach to these difficult conditions.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, Habibi et al found that hypertensive patients with LA enhancement were more inclined to persistent or permanent atrial fibrillation. 29 Therefore, our study adds to the current knowledge by providing new functional issues in patients with similar LV hypertrophy, but different pathophysiology, in an attempt to improve the therapeutic approach to these difficult conditions.…”
Section: Discussionmentioning
confidence: 91%
“…14,15 Moreover, increased atrial fibrosis contributes to atrial enlargement and functional impairment. 16 Although evidence is scarce, intrinsic atrial myopathy as part of the molecular disease has been suggested as well. 5 Specific sarcomeric gene mutations have recently been described in atypical forms of HCM that relate to juvenile onset of AF in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent development of a CMR technique that tracks LA wall motion using cine CMR imaging has shown promise as a good alternative for LA function assessment. 40 Further validation specifically in patients with AF is necessary.…”
Section: La Functionmentioning
confidence: 99%